Survey of NF1 inactivation by surrogate immunohistochemistry in ovarian carcinomas - Köbel, Martin; Yang, Rui Zhe; Kang, Eun Young; Al-Shamma, Zainab; Cook, Linda S.; Kinloch, Mary; Carey, Mark S.; Hopkins, Laura; Nelson, Gregg S.; McManus, Kirk; Vizeacoumar, Frederick S.; Vizeacoumar, Franco J.; et al. (Gynecologic oncology, 2023)
Objective - Inhibition of the MAPK pathway by MEK inhibitors (MEKi) is currently a therapeutic standard in several cancer types, including ovarian low-grade serous carcinoma (LGSC). A common MAPK pathway alteration in tubo-ovarian high-grade serous carcinoma (HGSC) is the genomic inactivation of neurofibromin 1 (NF1). The primary objectives of our study were to survey the prevalence of NF1 inactivation in the principal ovarian carcinoma histotype as well as to evaluate its associations with clinico-pathological parameters and key biomarkers including BRCA1/2 status in HGSC. - Methods - A recently commercialized NF1 antibody (clone NFC) was orthogonally validated on an automated immunohistochemistry (IHC) platform and IHC was performed on tissue microarrays containing 2140 ovarian carcinoma cases. Expression was interpreted as loss/inactivated (complete or subclonal) versus normal/retained. - Results - Loss of NF1 expression was detected in 250/1429 (17.4%) HGSC including 11% with subclonal loss. Survival of NF1-inactivated HGSC patients was intermediate between favorable BRCA1/2 mutated HGSC and unfavorable CCNE1 high-level amplified HGSC. NF1 inactivation was mutually exclusive with CCNE1 high-level amplifications, co-occurred with RB1 loss and occurred at similar frequencies in BRCA1/2 mutated versus wild-type HGSC. NF1 loss was found in 21/286 (7.3%) endometrioid carcinomas with a favorable prognostic association (p = 0.048), and in 4/64 (5.9%) LGSC, mutually exclusive with other driver events. - Conclusions - NF1 inactivation occurs in a significant subset of BRCA1/2 wild-type HGSC and a subset of LGSC. While the functional effects of NF1 inactivation need to be further characterized, this signifies a potential therapeutic opportunity to explore targeting NF1 inactivation in these tumors.